I IMPLEMENTASI METODE KITABAH DALAM PEMBELAJARAN TAHFIDZ PADA KELAS VII DI SMP TAKHASSUS AL-QUR’AN SULTAN FATTAH CILACAP - zahro, siti fatimatuz; Muhdi , Ali (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to describe and analyze the implementation of the kitabah method in tahfidz learning in class VII at SMP Takhassus Al-Qur'an Sultan Fattah Cilacap. The approach used is descriptive qualitative with field research methods. Data were obtained through observation, interviews, and documentation. From this study it was found that the implementation of the kitabah method in the school was carried out with initial planning in the form of making a structured schedule adjusted to the effectiveness of students in memorizing the Qur'an, namely in the morning at 08.00-10.00 WIB. Then, in its implementation, students who take part in the tahfidz program carry out stages such as writing verses of the Qur'an before memorizing, reading verses of the Qur'an before memorizing, submitting memorization and finally the evaluation process by correcting the reading starting from fluency, accuracy of pronunciation, and student memory. The effectiveness of the kitabah method in helping to strengthen memory is considered effective because this method makes it easier to memorize verses of the Qur'an, memorization becomes stronger, minimizes reading errors and makes it easier to understand the structure of the verses.